AI Research and Outlook of Social Science Perspective - Xu, Yinqing (International Journal of Computer Science and Information Technology, 2026)
AI has permeated into many social fields with its fast development. Meanwhile, it has a deep impact on society, economy and culture. AI’s applications improve industry efficiency and change the relationship among the labor market, social behavior mode, human being and technology. At the same time, ethical and social concerns such as data privacy, algorithm fairness come out of AI’s development. This study is aimed to discuss AI’s application in social science and the following challenges and opportunities. First of all, this study introduces basic concepts of AI and technical development. Secondly, this study discusses AI’s impact on social structure and ethic of AI decision-making. Thirdly, this study discusses how to use AI to do distinct research in social science. Finally, this study puts forward ethical and legal concerns in AI development, and suggests facilitating AI rational development through interdisciplinary collaboration. This study simultaneously proposes recommendations for policymakers to implement effective AI policies in sectors such as education, employment, and social welfare, to make sure that the benefits of AI technology are fairly and fully shared. This study also indicates increasing AI research from the perspective of social sciences and technological sciences, blending theory, pursue and investigate closely about AI ethics, so as to offer regulation guidance and support theory.